A Ratiometric Fluorescence Amplification Using Copper Nanoclusters with o-Phenylenediamine Sensor for Determination of Mercury (II) in Natural Water - Ampika Phoungsiri; Natee Lerdpiriyaskulkij; Pathavuth Monvisade; Ekarat Detsri; Arjnarong Mathaweesansurn (Sensors, 2023)
= 2.262). This demonstrated that the developed method could be applied for detecting mercury (II) in natural water samples.
Keywords: Nanocluster Synthesis and Applications; Mercury impact and mitigation studies; Advanced Nanomaterials in Catalysis